2016
DOI: 10.1098/rsos.160558
|View full text |Cite
|
Sign up to set email alerts
|

Automatic prediction of tumour malignancy in breast cancer with fractal dimension

Abstract: Breast cancer is one of the most prevalent types of cancer today in women. The main avenue of diagnosis is through manual examination of histopathology tissue slides. Such a process is often subjective and error-ridden, suffering from both inter- and intraobserver variability. Our objective is to develop an automatic algorithm for analysing histopathology slides free of human subjectivity. Here, we calculate the fractal dimension of images of numerous breast cancer slides, at magnifications of 40×, 100×, 200× … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 23 publications
4
76
0
Order By: Relevance
“…Fractal dimensions (19) have been used to characterize the irregular morphology of tumors (20)(21)(22) and vasculature (23,24) as well as subcellular structures such as mitochondria (25) and nuclei (26). There are numerous ways to calculate fractal dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractal dimensions (19) have been used to characterize the irregular morphology of tumors (20)(21)(22) and vasculature (23,24) as well as subcellular structures such as mitochondria (25) and nuclei (26). There are numerous ways to calculate fractal dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts to quantify the spatial heterogeneity of the tumor microenvironment include measuring the spatial colocalization of tumor and immune cells (13,14), locating immune cell clusters or "hotspots" (15,16), determining the amount of infiltration of lymphocytes into a tumor (17) and using Shannon entropy to quantify the cellular diversity (18). In addition, fractal dimensions (19) have been used to characterize the irregular morphology of tumors (20)(21)(22) and tumor-related structures (23)(24)(25)(26). (We review these approaches in more detail in the Discussion section.…”
Section: Introductionmentioning
confidence: 99%
“…We found that deep ResNet models were more sensitive and reliable than Inception in all tested cancer data-sets. We combined different magnification including 40X, 100X, 200X and 400X to generate comprehensive, independent and scalable system while a large number of previous studies employed single magnification level ( [7], [30]). Several other studies ( [7], [25], [48], [4]) also investigated multiple magnifications of medical images.…”
Section: Discussionmentioning
confidence: 99%
“…We combined different magnification including 40X, 100X, 200X and 400X to generate comprehensive, independent and scalable system while a large number of previous studies employed single magnification level ( [7], [30]). Several other studies ( [7], [25], [48], [4]) also investigated multiple magnifications of medical images. However, these approaches examined different classifiers for each magnification level and also had medical laboratory limitations to capture required multiple magnification to gather image training samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation